2010
DOI: 10.1111/j.1365-3180.2010.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Honeybees facilitate the invasion of Phyla canescens (Verbenaceae) in Australia – no bees, no seed!

Abstract: Several environmental weeds rely on the pollination services of introduced bees. The transfer of this knowledge to weed control management has not been fully explored. In part, this may be because it is difficult to quantify the economic impact of environmental weeds. This diminishes the prospects for expensive research and development required for integrated weed management. In this study, we examine the reproductive ecology of Phyla canescens, a species native to South America that is an aggressive agricultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…Additional measurements of the effect of A. saligna on interspecific pollen transfer within native communities, and its effect on seed set in native species, are needed. Furthermore, honeybees are generalist foragers that can facilitate the invasion of flowering alien plants (Gross et al, 2010), and more research is needed to determine their contribution to A. saligna pollination and reproductive success. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional measurements of the effect of A. saligna on interspecific pollen transfer within native communities, and its effect on seed set in native species, are needed. Furthermore, honeybees are generalist foragers that can facilitate the invasion of flowering alien plants (Gross et al, 2010), and more research is needed to determine their contribution to A. saligna pollination and reproductive success. …”
Section: Discussionmentioning
confidence: 99%
“…Our results also concur with a growing body of Table 1 Study site locations, focal species, and floral display metrics used in this study. Statistic and p values for comparing vegetation parameters between invaded and uninvaded plots can be found in Appendix D. Fabaceae n/a n/a n/a n/a n/a n/a 18°44.6E literature reporting the importance of honeybees in the pollination and spread of invasive flowering plants ( Barthell et al, 2001;Gross et al, 2010;Richardson et al, 2000a;Stout et al, 2002). Our observations of the broad spectrum of visitors to A. saligna adds support for the idea that the spread of invasive plant species is often not limited by a lack of suitable pollinators (Richardson et al, 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…data, 2006 whereas P. canescens is not capable of autogamous seed production, [18]). Our research has found that there is little geographic overlap in the species in either the native or Australian range (Figure 2) [17] respectively.…”
Section: Taxonomic Considerationsmentioning
confidence: 99%
“…Their distinction was based on leaf shape, leaf size, leaf apex characters and leaf indumentum. In this paper we follow the taxonomy of Kennedy [6] and Munir [8] because (i) the species are morphologically distinctive [6,8,17] ( Figure S1a,b); (ii) they appear to have a mostly non-overlapping distribution in their native range [6] and Australia [6,17]; (iii) have distinctive climatic preferences [8,17] and (iv) the species vary in their breeding biology (Fatemi, unpub data, see below; [18]). Table 1.…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation